The Use of Tocilizumab in 40 Patients With Polyarticular Juvenile Idiopathic Arthritis: the Results of a Retrospective Study - Mikhail M. Kostik; Irina A. Chikova; Eugenia A. Isupova; Margarita E. Dubko; Vera V. Masalova; Tatyana S. Likhacheva; Ludmila S. Snegireva; Ekaterina V. Gaidar; Olga V. Kalashnikova; Vyacheslav G. Chasnyk ("Paediatrician" Publishers LLC, 2017)
The issue of a therapy of children with juvenile idiopathic arthritis (JIA) with intolerance or insufficient effectiveness of methotrexate remains actual.Objective: Our aim was to study the efficacy and safety of tocilizumab in patients with polyarticular JIA.Methods. In a retrospective study, we studied the results of the use of tocilizumab in patients with active polyarticular JIA ( 5 active joints) resistant to prior therapy with methotrexate or a combination of methotrexate with other nonbiologic disease-modifying antiinflammatory drugs.Results. The data of 40 children (83% girls) with the onset median of polyarticular JIA of 4.8 (2.9, 8.1) years and the interval between the disease onset and the initiation of tocilizumab therapy of 5.7 (1.8, 8.5) years was analyzed. Tocilizumab was used as an intravenous infusion of 8 mg/kg (with a weight 30 kg) or 10 mg/kg (with a weight < 30 kg) every 4 weeks. The duration of tocilizumab monotherapy in 5 (13%) children was 1,109 days (452; 1,542). The stages of inactive disease (according to the criteria of C. Wallace, 2004) in 6 months of tocilizumab therapy reached 6 (15%) patients, in 42 months - 32 (80%) patients. In 3 patients, tocilizumab was canceled due to persistent remission. After 6 months of treatment, there was a marked decrease in erythrocyte sedimentation rate, C-reactive protein concentration, number of leukocytes and platelets (in all cases, p < 0.001) to normal values, which persisted throughout the whole period of drug administration. Predictors for achieving inactive disease were the initial (at the onset of tocilizumab therapy) number of peripheral blood leukocytes < 9.0X109/l [relative risk (RR) 1.92; 95% confidence interval (CI) 0.9-4.6)] and the absence of prior biological therapy (RR 1.92, 95% CI 0.9-4.6). The most frequent side effects of tocilizumab therapy were transient hypercholesterolemia (in 13), hypertriglyceridemia (in 4), transient grade II neutropenia (in 1).Conclusion. The long-term efficacy and relative safety of tocilizumab in children with polyarticular JIA have been showed.